206k views
5 votes
Simplify the expression where possible. (6^3)^-3

User Gakuo
by
5.8k points

2 Answers

3 votes


\bf ~\hspace{7em}\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} ~\hspace{4.5em} a^n\implies \cfrac{1}{a^(-n)} ~\hspace{4.5em} \cfrac{a^n}{a^m}\implies a^na^(-m)\implies a^(n-m) \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ (6^3)^(-3)\implies 6^(-3\cdot 3)\implies 6^(-9)\implies \cfrac{1}{6^9}\implies \cfrac{1}{10077696}

User Slugster
by
6.3k points
2 votes

I think the answer is 6^9.



User SandeliusME
by
6.2k points